GEOCHEMICAL CHARACTERISTICS OF CRUDE OILS FROM THE SHARARA‐C OIL FIELD, MURZUQ BASIN, SOUTHWESTERN LIBYA. (22nd December 2022) - Saheed, Ramadan Musbah M.; Knudsen, Tatjana Šolević; Faraj, Musbah Abduljalil M.; Nytoft, Hans Peter; Jovančićević, Branimir
Abstract : Crude oil samples from the Sharara‐C oil field (Concession NC‐115, Murzuq Basin, SW Libya) were analysed by organic geochemical methods in order to infer the geochemical characteristics of their respective source rocks. Aromatic hydrocarbons were analysed by gas chromatography – mass spectrometry (GC‐MS), and gas chromatography – tandem mass spectrometry (GC‐MS‐MS) was used to analyse saturated biomarkers. The Sharara‐C oils are interpreted to have been generated by marine shales containing mixed terrigenous and marine organic materials deposited in an intermediate (suboxic) environment. Age‐specific biomarker ratios indicated that the oils are older than Cretaceous, and maturation‐related parameters pointed to their high thermal maturity. Consistent with previous studies, source rocks are inferred to be "hot" shales in the Lower Silurian Tanezzuft Formation. Almost all the parameter ratios calculated varied over a very narrow range, indicating that the investigated oils were compositionally similar. The only significant difference that was noted concerned the sterane/hopane ratios whose variation suggested that there was some variability in the composition of the source organic material. The organic geochemical parameters determined for the Sharara‐C crude oils were compared with published data on other crude oils from Concession NC‐115. Almost all the parameters agreed well with previously published data on oils from this part of the Murzuq Basin. The greatest deviation concerned the values of some of the maturity parameters. This tended to confirm the conclusions of previous studies concerning the presence of a number of distinct oil families and sub‐families in the Sharara oil field area which are genetically related but which have different maturities.